(untitled) (Journal of Comparative Social Work, 2016)
In this article, I reflect on my experiences using institutional ethnography to support socially just policy, practice and organizational change. I focus specifically on three inter-related institutional ethnographic research projects that have informed my approach to working with social workers, shelter workers, lawyers, policy analysts, community organizers, teachers, probation officers and youth to create change. Although strategic collaborations to change institutional practices and knowledge are rife with tensions, I show how institutional ethnography can be used reflexively throughout the collaborative process to create conditions for critical consciousness-raising among participants; inspire reflection and action on the part of human service professionals and inform collective efforts to create systemic change, as well as to guide the research process itself. I conclude by suggesting that institutional ethnographers seeking to influence socially just change need to find ways to balance the demands of academic writing, while being true to the activist origins of this sociological approach.